Optimizing Local Resources in the Development of the Maritime Defense Industry Ecosystem in Indonesia - Sukrisna, Cecep; Marsetio; Bura, Romi S.; Widodo, Pujo (International Journal of Science and Society, 2025)
The development of the maritime defense industry ecosystem is a strategic step in increasing national defense independence. This research aims to optimize the use of local resources in the maritime defense industry to reduce dependence on imports and increase the competitiveness of the domestic industry. The methods used include descriptive-qualitative analysis with a literature study approach, interviews with stakeholders, and case studies on the application of local technologies and materials in the maritime defense industry. The results of the study show that local resources, natural fiber-based composite materials, domestically produced high-strength steel, as well as experts in the field of maritime engineering, have great potential in supporting the defense industrial ecosystem. However, the challenges of limited technology, infrastructure and regulations have not fully supported it, so it is still an obstacle. In conclusion, the optimization of local resources can be carried out through synergy between the government, industry, and research institutions in technology development, human resource capacity building, and policies that support innovation and investment. The strategic implications of the research on defense policy are that the maritime defense industry based on local resources is a solution in maintaining national maritime sovereignty and security.